Sovereign bond markets and financial volatility dynamics: Panel-GARCH evidence for six euro area countries - Ribeiro, P. P.; Cermeño, R.; Curto, J. D. (Finance Research Letters, 2017)
This paper investigates, over 2007.01–2016.06, the determinants of six euro area sovereign bond yield spreads through original Panel-GARCH models that incorporate key features of volatility dynamics, such as extreme persistence, asymmetry and risk premia effects. Overall, EMU sovereign bond yield spreads are markedly geared by differences in creditworthiness and liquidity and also tend to reflect economic conditions and agents’ risk appetite. Moreover, we find significant and quite persistent conditional volatility, and there is evidence that higher yield spreads become less predictable, although the presence of asymmetric effects on the volatility process seems negligible. Definitely, these results have important policy implications.